Day 1 Mon, November 09, 2020 2020
DOI: 10.2118/202981-ms
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Waterless Fracturing Fluids: A Review

Abstract: Hydraulic fracturing technology has grown popular with the rapidly increasing development of tight conventional and unconventional reservoirs. A major concern with this technique is the use of large amounts of water in these treatments. The use of water causes many potential damaging issues in the formation and limits the amount that can be saved for future generations. One solution is waterless fracturing treatments, which were developed to reduce or eliminate the need for water in hydraulic fracturing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 135 publications
0
12
0
Order By: Relevance
“…Ostwald ripening is a thermodynamically driven mechanism occurring due to larger particles being more energetically favored than smaller particles in a heterogeneous system like foam. After the foam formation, the smaller foam bubbles shrink while the bigger ones grow over time [26,27]. Due to big foam bubbles being generally less stable, Ostwald ripening leads to the overall foam system instability.…”
Section: Bottle Foam Tests At Ambient Conditionsmentioning
confidence: 99%
“…Ostwald ripening is a thermodynamically driven mechanism occurring due to larger particles being more energetically favored than smaller particles in a heterogeneous system like foam. After the foam formation, the smaller foam bubbles shrink while the bigger ones grow over time [26,27]. Due to big foam bubbles being generally less stable, Ostwald ripening leads to the overall foam system instability.…”
Section: Bottle Foam Tests At Ambient Conditionsmentioning
confidence: 99%
“…At this point, it is important to address the economic considerations regarding the field application of n-heptane (or light alkanes) as a frac-fluid. Studies for the application of hydrocarbon-based fluids have demonstrated economically attractive prospects and shown that comparable or even lower costs will be incurred in comparison with waterbased fluids due to lower well cleanup requirements, better flowback ability, less additives, injection fluid flowback, reuse or sale, no special disposal requirements, and increased productivity [22,[55][56][57][58][59][60]. Moreover, unlike gas-based hydrocarbon fluids such as LPG, there is no need for compression for liquification for the fluid reuse [61].…”
Section: Design Proposalsmentioning
confidence: 99%
“…Obtaining fresh water has become difficult in some fields due to the high water transportation costs from the source to the wellsite, as well as rising limits on freshwater supply . Conventional wells use 200 000 gallons of water for hydraulic fracturing, while unconventional wells can use up to 16 million gallons. For example, fracturing shale and tight sandstone formations often require more than 1 million gallons (3700 m 3 ) of water per well . This method uses a lot of water, damages the formation, and restricts future savings.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is vital to examine alternatives to water-based fracturing fluids that support the preservation of water and encourage sustainable growth. Waterless hydraulic fracturing procedures can reduce or eliminate water use . It has become essential to find ways to optimize hydraulic fracturing operations in order to utilize less fresh water and more green additives.…”
Section: Introductionmentioning
confidence: 99%